2021
DOI: 10.48550/arxiv.2108.06686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Statistical modeling of adaptive neural networks explains coexistence of avalanches and oscillations in resting human brain

Abstract: Brain dynamics display collective phenomena as diverse as neuronal oscillations and avalanches. Oscillations are rhythmic, with fluctuations occurring at a characteristic scale, whereas avalanches are scale-free cascades of neural activity. Here we show that such antithetic features can coexist in a very generic class of adaptive neural networks. In the most simple yet fully microscopic model from this class we make direct contact with human brain resting-state activity recordings via tractable inference of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…In this paper, we provided a description of the resting-state brain activity that uncovers the dynamic organization of neural activity cascades underlying brain oscillations, unifying two complementary approaches to neural synchronization—neuronal avalanches and oscillations [8, 22, 32, 39, 30, 34]. Our analysis shows that the collective neural dynamics underlying resting-state brain activity is governed by attenuation-amplification principles across timescales—which we link with prominent features of the alpha oscillations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper, we provided a description of the resting-state brain activity that uncovers the dynamic organization of neural activity cascades underlying brain oscillations, unifying two complementary approaches to neural synchronization—neuronal avalanches and oscillations [8, 22, 32, 39, 30, 34]. Our analysis shows that the collective neural dynamics underlying resting-state brain activity is governed by attenuation-amplification principles across timescales—which we link with prominent features of the alpha oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, simultaneous investigations of oscillations and avalanches in the human brain selectively focused on long-range temporal correlations in alpha amplitude fluctuations and on avalanche scaling features [43, 71]. At the same time, models capturing the simultaneous emergence of avalanches and oscillations concentrate on generic underlying mechanisms and signatures of criticality [48, 17, 24, 34]. In particular, a quantitative analysis of awake resting-state brain activity through a novel class of adaptive neural networks recently linked this coexistence to proximity to a non-equilibrium critical point at the onset of self-sustained oscillations [14, 34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, recent studies suggest that criticality plays a key role in determining the temporal organization of sleep stage and arousal transitions (Lombardi et al, 2020a;Wang et al, 2019) The exponent k has been previously measured in the awake resting-state, from Zebrafish and rats to monkeys and humans (Ponce-Alvarez et al, 2018;Miller et al, 2019;Fontenele et al, 2019;Lombardi et al, 2021a;Mariani et al, 2021;Dalla Porta and Copelli, 2019). In line with our findings, Miller et al (Miller et al, 2019) found that, in awake monkeys, k ≃ 2 in the range corresponding to the power law regime of the size and duration distributions, while k ≃ 1 − 1.5 in the region that corresponds to the exponential cut-off of the distributions-where we found k ≈ 1.3.…”
Section: Brain Dynamics and Criticality During Sleepmentioning
confidence: 99%